A new Co(II)‐coordination polymer: Photocatalytic studies and treatment values on mania by reducing the ErbB4 expression on the noradrenergic neurons. Issue 8 (24th March 2021) - Zhou, Yun‐Shan; Wang, Jia; Lin, Xiao‐Fang; Jiang, Qiuhua; Zhu, Jian‐Nan
Abstract: A novel coordination polymer based on Co(II) has been generated utilizing the 4, 4′, 4″‐phosphanetriyltribenzoic acid (H3 tpp) as the tritopic connector in the existence of a second N‐donor ligand 3, 3′‐bipyridine (3, 3′‐bpy) under the solvothermal reaction conditions, and its chemical formula is [Co3 (tpp)2 (3, 3′‐bpy)]·7DMF (1 ). Moreover, under ultraviolet irradiation, complex 1 has high photocatalytic activities for methylene blue degradation, and its photodegradation performance does not show much reduction after three cycles of experiments. Furthermore, the compound's biological activity against the mania was assessed, and the protentional mechanism was discussed. First, the neuroregulin1 content in the hippocampus was detected via enzyme‐linked immunosorbent assay to evaluate the compound's treatment activity on mania. Then, the ErbB4 relative expression levels were detected using real‐time reverse transcription‐polymerase chain reaction. The carboxyl groups have been confirmed to be responsible for all the binding interactions formed by molecular docking simulation. Abstract : A novel Co(II)‐based coo"rdination polymer has been prepared, which shows high photocatalytic activities for MB degradation and photocatalytic stability even after three cycles' experiments. Furthermore, the compound's biological activity against the mania was assessed, and the protentional mechanism was discussed.